Charging protocols for lithium-ion batteries and their impact on cycle life—An experimental study with different 18650 high-power cells. (May 2016) - Keil, Peter; Jossen, Andreas
Graphical abstract: Highlights: Comparison of various charging protocols under identical environmental conditions. Cycle life for continuous and pulsed charging with different currents and voltages. Three cell types reveal differences among cell chemistries and manufacturers. Impact of charging protocols on capacity utilization, charging time, and efficiency. Recommendations for optimized charging strategies. Abstract: This paper presents an overview on charging strategies for lithium-ion batteries. Moreover, a detailed assessment of charging strategies is performed, based on an extensive experimental study with three different cell types. The experimental results reveal that the impact of charging currents and charging voltages on cycle life can vary markedly among different lithium-ion batteries. In general, the cycle life is influenced more by high charging currents than by high discharging currents. Different boost charging protocols have disclosed that high charging currents can deteriorate cycle life not only at high state of charge (SoC), but also at very low SoC. Our investigations on pulse charging show that lithium-ion cells withstand charging pulses of high current or high voltage without any deterioration in cycle life, when the duration of the pulses remains short and the mean current and voltage values are considerably lower. For pulses of less than 1 s, cycle life has been similar for pulsed and continuous charging with the same mean charging currents and identical cycle depths. This paper also presents the impact of charging currents and charging voltages on capacity utilization, charging time, and efficiency to support the development process of optimized charging protocols for practical applications.